2013
DOI: 10.1111/dom.12148
|View full text |Cite
|
Sign up to set email alerts
|

Olanzapine increases hepatic glucose production through the activation of hypothalamic adenosine 5′‐monophosphate‐activated protein kinase

Abstract: Our results indicate that olanzapine activates AMPK in the hypothalamus, which increases hepatic glucose production via the sympathetic nervous system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
47
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 43 publications
1
47
0
2
Order By: Relevance
“…Furthermore, acute central olanzapine administration in rodents was found to induce hyperglycemia only in a postprandial state (where one would expect elevated physiologic levels of insulin or glucose that reach the brain) in association with increases in key gluconeogenic enzymes in the liver. 28 This effect was not observed in fasted rodents receiving a central olanzapine infusion. 28 Our data, taken together with the aforementioned evidence, suggest that a central insulin …”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Furthermore, acute central olanzapine administration in rodents was found to induce hyperglycemia only in a postprandial state (where one would expect elevated physiologic levels of insulin or glucose that reach the brain) in association with increases in key gluconeogenic enzymes in the liver. 28 This effect was not observed in fasted rodents receiving a central olanzapine infusion. 28 Our data, taken together with the aforementioned evidence, suggest that a central insulin …”
Section: Discussionmentioning
confidence: 96%
“…28 This effect was not observed in fasted rodents receiving a central olanzapine infusion. 28 Our data, taken together with the aforementioned evidence, suggest that a central insulin …”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…36) Thus, the serum concentrations of olanzapine in the present study were higher than those at clinical doses of olanzapine. Though acute hyperglycemias were reported in patients treated with 2.5-10 mg/d of olanzapine, 6,7) it is still unknown about the concentrations of olanzapine at the onset of acute hyperglycemia in clinical setting. Therefore, the concentration-effect relationship of olanzapine-induced acute hyperglycemia in humans remains to be solved.…”
Section: Discussionmentioning
confidence: 99%
“…Mizukami et al described a 22-year-old woman without diabetes who developed hyperglycemia (her glucose concentration exceeded the detection limits) 4 h after the first administration of olanzapine. 7) Regarding the mechanism responsible for the induction of acute hyperglycemia by olanzapine, Ikegami et al recently showed that olanzapine activates adenosine 5′-monophosphate-activated protein kinase (AMPK) in the hypothalamus, which increases the hepatic production of glucose via the sympathetic nervous system. 8) They also suggested that olanzapine activates hypothalamic AMPK by antagonizing histamine H 1 , dopamine D 2 , and α 1 -adrenergic receptors.…”
mentioning
confidence: 99%